Feasibility of Capacitive Aptasensor on Paper to Detect Pathogenic Bacteria Responsible for Nosocomial Infection. (2017) - Raberalam, T.; Balde, M.; Hantova, S.; Vena, A.; Marchandin, H.; Sorli, B.
Abstract: Nosocomial infections are contracted in a hospital or health care facility. Bacterial cause is the most common in 87% of cases. Studies have been conducted for the detection of these bacteria. The aim of this biosensor is to make an early detection tool, easy to use, reliable, not invasive and low cost. The goal is to detect in real time and simultaneously in a small amount of body fluids such as urine, sweat or saliva, the major bacterial pathogens causing these diseases: Escherichia Coli, Pseudomonas aeroginosa, Acinetobacter baumannii, Staphylococcus aureus and Clostridium difficile.